Money market rates and retail interest regulation in China: The disconnect between interbank and retail credit conditions - Nathan Porter; TengTeng Xu (Bank of Canada, 2013)
Interest rates in China are composed of a mix of both market-determined interest rates (interbank rates and bond yields), and regulated interest rates (retail lending and deposit rates), reflecting China's gradual process of interest rate liberalization. This paper investigates the main drivers of China's interbank rates by developing a stylized theoretical model of China's interbank market and estimating an EGARCH model for 7-day interbank repo rates. Our empirical findings suggest that movements in administered interest rates (part of the People's Bank of China's monetary policy toolkit) are important determinants of market-determined interbank rates, in both levels and volatility. The announcement effects of reserve requirement changes also influence interbank rates, as well as liquidity injections from open market operations in recent years. Our results indicate that the regulation of key retail interest rates influences the behaviour of marketdetermined interbank rates, which may have limited their independence as price signals. Further deposit rate liberalization should allow short-term interbank rates to play a more effective role as the primary indirect monetary policy tool.
Keywords: E43; E52; E58; C22; 330; Development economics; Econometric and statistical methods; Financial markets; Monetary policy framework; Transmission of monetary policy